Antimicrobial film from jackfruit waste powder incorporating clove and ginger essential oils and its application in food packaging - Ronakit Nimitr; Phutthipong Eamsiriluck; Daniel Tua Purba; Winatta Sakdasri; Warawut Krusong; Rattiya Waeonukul; Pichayada Somboon (Applied Food Research, 2025)
• Bioactive packaging films were developed using PVA reinforced with jackfruit peel waste and essential oils. • FTIR and SEM analysis confirmed that hydrogen bonding chemically anchors oil droplets to the polymer matrix. • Ginger-incorporated films displayed superior thermal resistance over clove films. • Clove films demonstrated exceptional antioxidant activity (90% DPPH inhibition), while Ginger films offered broader antimicrobial efficacy against resistant strains. • The films extended the shelf life of fresh poultry and bread by suppressing spoilage odors through controlled bioactive release. Bioactive composite films were developed utilizing a polyvinyl alcohol (PVA) and jackfruit waste powder (JK PW) matrix, functionalized with either ginger (JK PW–GEO) or clove essential oil (JK PW–CEO). Structural characterization indicated that the essential oils were chemically anchored to the polymer matrix via intermolecular hydrogen bonding, facilitating the formation of a cohesive micro-composite architecture. These chemical interactions significantly enhanced thermal stability; notably, JK PW–GEO films exhibited superior thermal resistance (limiting mass loss to 9% within the 180–260°C range) compared to JK PW–CEO films (∼14% loss). This stability is attributed to the robust retention of non-volatile gingerols within the hydrogen-bonded network, as confirmed by HS-GC-MS/MS analysis. Regarding functional bioactivity, distinct performance profiles were observed: JK PW–CEO films demonstrated exceptional antioxidant capacity (334.75 mg GAE/g; 90.62% DPPH radical scavenging), whereas JK PW–GEO films exhibited broader antimicrobial efficacy, particularly against resistant bacterial strains such as Bacillus subtilis and Salmonella enterica . In practical application trials, both film formulations effectively extended the shelf life of bread and fresh poultry by mitigating microbial proliferation and suppressing spoilage odors. Sensory evaluation confirmed that the films maintained desirable olfactory profiles, thereby enhancing the perceived quality of the packaged products. Collectively, this study establishes that JK PW-based composites offer a sustainable avenue for active packaging, wherein ginger oil provides superior thermal and antimicrobial stability, while clove oil delivers potent antioxidant protection.
Keywords: Nanocomposite Films for Food Packaging; Essential Oils and Antimicrobial Activity; Polymer Science and PVC